Salt Quality Determination Using Simple Additive Weighting (SAW) and Analytical Hirarki Process (AHP) Methods - Ach Khozaimi; Yoga Dwitya Pramudita; Eka Mala Sari Rochman; Aeri Rachmad (Universitas Trunojoyo Madura, 2019)
Salt has a salty taste obtained by drying seawater into mineral crystals. However, the quality of industrial salt in Indonesia is still an obstacle, so the need for industrial salt still relies on imported salt. The quality of salt is shown from physical and chemical appearance. Good salt is shown by the crystal form which is smooth and has a clear white color. Good salt quality knowledge must be known so that it can meet Indonesia's national standards and can distinguish salt designation based on its quality category. This study compares the Simple Additive Weighting (SAW) and Analytical Hierarchy Proccess (AHP) methods to determine the highest quality salt. The SAW method gives weight to each of its attributes and the total score finally produces an alternative decision that matches the criteria, thus producing a high-quality salt. While the AHP method starts by creating a hierarchical structure that has the main objectives, criteria, sub criteria and alternatives to be discussed. Pairwise comparisons are used to form relationships in the structure. So it will form a matrix where the ratio scale is derived in the form of the main vector eigen or function-eigen.